Analisis Perencanaan Dan Pelaksanaan Anggaran, Sumber Daya Manusia, Pengadaan Barang Jasa Dan Lingkungan Birokrasi Terhadap Penyerapan Anggaran Di Kabupaten Kediri - Indah Purwati; Arisyahidin Arisyahidin; Abu Talkah (Otonomi, 2021)
Absorption of local government budgets is the accumulation of budget absorption carried out by each Institution, and can be one of the indicators in assessing the financial management performance of a region, because through the level of budget absorption it can be seen the description or performance and capabilities of a region. The region implements and is responsible for every planned activity. Budget absorption in Kediri Regency during the 2016 - 2020 period reached the range of 81.68% - 88.79%. This study aims to identify and analyze the factors that are considered dominant in influencing budget absorption in Kediri Regency, namely budget planning and implementation, human resources, procurement of goods and services, and the bureaucratic environment. Sources of data in the form of primary data and secondary data. Primary data in the form of questionnaires were distributed based on purposive random sampling to 15 institutions with the largest budget in Kediri Regency. The research method used is quantitative using Multiple Linear Regression Analysis. This study uses 5 (five) independent variables, namely budget planning (X1), budget execution (X2), human resources (X3), procurement of goods and services (X4), bureaucratic environment (X5), and 1 (one) dependent variable. . variable. namely budget absorption (Y). The results showed that the five independent variables simultaneously had a positive effect on budget absorption. Partially, the variables of budget planning, budget execution, human resources and procurement of goods and services have a positive effect on budget absorption, while the bureaucratic environment variable has a negative effect on budget absorption. Partially, the variable that has the most dominant influence on budget absorption is the Procurement of Goods and Services. Overall, the magnitude of the influence of budget planning, budget execution, human resources, procurement of goods and services and the bureaucratic environment on budget absorption is explained by the determination value of 41%, while 59% is influenced by other factors outside the study